Character Development of Estella/Cruella in Cruella (2021) Movie - Nisa Meisa Zarawaki; Andang Saehu; Nurholis Nurholis; Toneng Listiani (J-Lalite: Journal of English Studies, 2022)
This research focuses on process of identifying the main character’s character development starts by unravelling (1) the characterizations of the main character; (2) the conflicts experienced by the main character; and (3) the character development of main character. The researcher uses the theory of Petrie & Boggs to define character, conflict, and character development. Qualitative descriptive methods and analysis content are used to analyze deep problems to find the answers. The result showed that the conflicts happened to the main character are coming from internal conflict between Cruella and herself and external conflicts between Cruella and Catherine, Baroness, and the society. Also, the development of Cruella character is triggered by conflict, it is shown by the character's development constantly grew when enter the new act/story